Multi-purpose dams of the Pacific Northwest (Bonneville Power Administration, 1976)
A tour in photographs of 56 hydroelectric projects in the Pacific Northwest, including 31 dams of the Federal Columbia River Power System, and 25 major non-Federal installations in the Pacific Northwest.